Analysis of Factors Affecting Employee Performance at Aetra Regional Drinking Water Company of Jakarta (PDAM) - Yunita Fajar Sari; Rukun Santoso; Erwin Permana; Wiwin Wiwin; Ratih Ayu S (Ilomata International Journal of Management, 2022)
The research at Aetra Air Drinking Water Regional Company of East Jakarta (PDAM) aims to analyze: 1) the influence of work discipline on employee performance, 2) The Effect of Occupational Safety and Health (K3) on employee performance. 3) The simultaneous influence of work discipline and Occupational Safety and Health (K3) on employee performance. The research approach used quantitative paradigms. The population was 339 people and the determination of samples used the Slovin technique so that a sample of 77 respondents was obtained. Data analysis used a co-existing linear regression test by using SPSS. The results show that Work Discipline and Occupational Safety and Health (K3), both simultaneously and significantly affect the performance of employees of PT. AETRA AIR Jakarta, while the managerial implication of these findings is the need for efforts to improve the employee performance of PT. AETRA AIR Jakarta. Referring to the findings of this study, among others, there is a need for firmness from the agency about the employees’ problems, especially for those whose absence rate is high enough to improve discipline. The reason is that the problem of indiscipline affects other employees so that it will affect the overall performance of the company. This research shows that matters related to discipline, and Occupational Safety and Health (K3) should be more considered and always improved to further boost the employee performance at PT Aetra Air Jakarta. Discipline should be improved in terms of supervision from HRD while Occupational Safety and Health (K3) involves other parties/agencies in terms of the Occupational Safety and Health (K3) management system.